Screening of Indian Germplasm of Jatropha curcas for Selection of High Oil Yielding Plants - Kaushik, Nutan; Roy, Sumit; Biswas, Gopal C. (Indian Journal of Agroforestry, 2020)
More than one thousand samples of Jatropha seeds representing twelve states of India were analysed for oil content and kernel seed coat ratio. The seed oil content varied from 25-44% and the Kernel and Seed Coat ratio (KlSC) varied from 0.36-2.12.328 plants having more than 35% seed oil content have been identified so far. Based on the percentage of higer oil yielding plants, the states could be divided into seven groups. Uttranchal recorded highest percentage of high 011 yielding plants 73%. Samples with less than 1.5 K/SC ratio recorded lower average 011 content (<30%).